Gambling decision determinants : difficulty, stakes and self-determination. - Ong, Sabrina Ee Ying. (2009)
The primary aim of this study is to investigate the influence of external factors, level of difficulty, and stakes involved; and internal factor, self-determination, on gambling decisions. The study is also interested to examine the influence of these factors on two groups which researchers have previously cautioned to be prone to gambling problems, namely the young adults group, and middle-aged male adults group. Participants completed the Self-determination Scale (Sheldon and Deci, 1996) and a computerized task designed for this study. Level of difficulty was found to consistently influence both groups significantly [ F(1,88)= 37.23, p< .05; F(1, 18) = 8.31. p< .05]. Stakes, comprising of the payout and loss components, have significant effect for the loss amount [ F(1,89) =369.02, p < .05; F(1,39) = 79.64, p =.000] and interaction effect [F(1,89) = 8.68, p < .05; F(1, 39 = 9.13, p = .00] in both groups; while only influencing the groups of young adults significantly for the payout amount [ F(1,89) = 8.31, p < .05]. The only internal factor studied -self-determination, was found to be significantly decreasing the interaction effect between payout and loss amount for high self-determination group for the young adult group only.